Business cycle and innovation activity in medium-high and high technology industry in Poland - Dzikowski Piotr (Management, 2015)
This article examines differences in an impact of business cycle phases on innovation activity in medium-high and high technology industry in Poland. It is assumed that each business cycle phase influences innovation activity in the same fashion, but its impact varies and it depends on the firm’s innovation activity. The higher innovation activity the less impact of business cycle. The scope of the survey relates to innovation in MHT and HT industry in Poland. The data concerns the innovation at the firm level and the diffusion “new for the company”. Innovation activity is defined by the following activities: (1) expenditure on research and development and investments in fixed assets not used so far such as: a)buildings, premises and land; b) machinery and equipment, c) computer software; (2) implementation of new products and technological processes and (3) innovation cooperation. The methodological part of the analysis includes a logit modeling. The survey includes 1355 companies. Business cycle has a great influence on innovation activity in MTH and HT industry in Poland. The influence of recovery phase is positive whereas both stagnation and recession phases decrease the probability of innovation activity. The character of influence depends on the propensity to take innovation activity. The higher level of innovation activity the enterprises present the less influence of business cycle they get.